2017
DOI: 10.21475/ajcs.17.11.08.pne339
|View full text |Cite
|
Sign up to set email alerts
|

Participatory assessment of potato farming systems, production constraints and cultivar preferences in Uganda

Abstract: Potato (Solanum tuberosum L.) is a major food and cash crop mainly grown by small-scale farmers in the highland regions of Uganda. Farmer practices and constraints in potato production and management differ from one area to another and so are desired attributes. A survey was conducted in eight major potato producing districts of Uganda. The study districts were from Central, Eastern and South Western regions of the country. The survey was carried out from May to August 2015. A semi-structured questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Other varieties are; Rwangume, Nakpot 1, Sankena, Civilian, Megabond, Cruza and Kachpot 1 (Tatwangire and Nabukeera, 2017). According to Namugga et al (2017), Rwangume and Victoria are the commonly grown varieties in South Western, Eastern and Central regions. A list of selected potato varieties with their sensory, post-harvest and morphological attributes is shown in Table 1.…”
Section: Section I: Food Science Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other varieties are; Rwangume, Nakpot 1, Sankena, Civilian, Megabond, Cruza and Kachpot 1 (Tatwangire and Nabukeera, 2017). According to Namugga et al (2017), Rwangume and Victoria are the commonly grown varieties in South Western, Eastern and Central regions. A list of selected potato varieties with their sensory, post-harvest and morphological attributes is shown in Table 1.…”
Section: Section I: Food Science Varietiesmentioning
confidence: 99%
“…In parts of Eastern Uganda (Kapchorwa), key varietal attributes according to farmers include: storability, high dry matter and flesh color while in South Western Uganda (Kabale and Kisoro) it was tuber size (CIP, 2018). According to Namugga et al (2017), preferred attributes by farmers include red skinned and yellow fleshed potatoes which are associated with good eating quality. Katundu et al (2010) reported that consumers look out for potatoes with smooth skin, no sprouting, no blemishes and no greening when purchasing at the marketplace.…”
Section: Raw Potato Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the year of 2017, Uganda had an annual potato production of 173,244 tons harvested from an area of 39,374 ha [3]. The potato crop in Uganda, especially in the districts of Kabale and Kisoro is a major source of food and cash income [4]. Majority of the potato produced is increasingly being processed into chips and crisps through retail outlets and home consumption [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing importance of processing in the Ugandan potato industry, there is limited availability of potato varieties within the Ugandan market with specific infusion of particular tuber processing attributes to fit into the processing and marketing chain. These processing attributes of dry matter content and reducing sugars have not received sufficient research attention in Uganda as there seems to be limited information regarding their inheritance, and this together with the few available varieties possessing quality processing attributes has resulted into a demand deficit which is bound to affect the income security of the resource poor farmers in the highland areas as they sell 60 -70% of their crop production [4,5,6,7]. Processing attributes of dry matter content and reducing sugars are quantitative traits that are affected by genetic factors of the plant besides environmental conditions [8].…”
Section: Introductionmentioning
confidence: 99%